2004
DOI: 10.1016/j.clpt.2004.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Functional impact of CYP2C9*5, CYP2C9*6, CYP2C9*8, and CYP2C9*11 in vivo among black Africans*1

Abstract: The CYP2C9*5 and *6 alleles are associated with decreased enzyme activity in vivo compared with the wild-type variant, whereas the CYP2C9*8 and *11 variants did not appear to have large in vivo effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
62
1
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(68 citation statements)
references
References 30 publications
4
62
1
1
Order By: Relevance
“…The two clinically most important alleles, CYP2C9*2 and CYP2C9*3, occur at a minor allele frequency of ϳ10 and 6%, respectively, in white populations but are less abundant or undetectable in individuals of African and Asian descent (Lee et al, 2002). In contrast, other potentially important variants, e.g., CYP2C9*8, *9, and *11, occur in the African population with frequencies of 3.6, 13, and 5.6%, respectively, whereas these alleles, in turn, are low or undetectable in other racial groups (Allabi et al, 2004;Blaisdell et al, 2004). Convincing evidence suggests that CYP2C9*2 and CYP2C9*3 alleles convey reduced enzyme activity and have been associated with drug dosage requirements and treatment outcomes (Aithal et al, 1999;Higashi et al, 2002;Lee et al, 2002).…”
Section: Introductionmentioning
confidence: 94%
“…The two clinically most important alleles, CYP2C9*2 and CYP2C9*3, occur at a minor allele frequency of ϳ10 and 6%, respectively, in white populations but are less abundant or undetectable in individuals of African and Asian descent (Lee et al, 2002). In contrast, other potentially important variants, e.g., CYP2C9*8, *9, and *11, occur in the African population with frequencies of 3.6, 13, and 5.6%, respectively, whereas these alleles, in turn, are low or undetectable in other racial groups (Allabi et al, 2004;Blaisdell et al, 2004). Convincing evidence suggests that CYP2C9*2 and CYP2C9*3 alleles convey reduced enzyme activity and have been associated with drug dosage requirements and treatment outcomes (Aithal et al, 1999;Higashi et al, 2002;Lee et al, 2002).…”
Section: Introductionmentioning
confidence: 94%
“…Whether an altered conversion of losartan to EXP3174 is associated with an altered blood pressure response to losartan remains unclear, as this was observed in Japanese (Sekino et al, 2003) but not Caucasian healthy volunteers (Lee et al, 2003b); however, the subject groups being tested were small, and ARBs typically cause only minor blood pressure reductions in healthy subjects to begin with. Later studies based on black African subjects found that the *5 and *6 alleles of CYP2C9 are also associated with lower enzyme activity for losartan conversion in vivo, whereas the *8 and *11 alleles had little effect (Allabi et al, 2004). The *13 allele of CYP2C9 was also reported to be associated with a reduced conversion of losartan to EXP3174 in healthy volunteers (Li et al, 2009b).…”
Section: H Pharmacokinetic Pharmacogenomicsmentioning
confidence: 99%
“…CYP2C9*6 (818delA, frameshift) contains a premature stop codon, resulting in a null allele that dramatically decreases the metabolism of phenytoin and warfarin. [31,32]Based on studies with recombinant CYP2C9 [25,26] CYP2C9*11 is predicted to have greatly diminished catalytic activity, but has not received extensive clinical study. One study [38] reported significantly lower warfarin dose requirements in patients with the CYP2C9*1/*11 genotypes compared to those with CYP2C9*1/*1 genotype.…”
Section: Discussionmentioning
confidence: 99%
“…[25,26] Therefore, this variant was also included in this study. The *10 allele (A815G, E272G) is a rare allele reported in European Americans.…”
Section: Cytochrome P450 2c9 (Cyp2c9) Genotype Determinationmentioning
confidence: 99%